Comparison of early versus standard timing for silicone stent removal following External Dacrocystorhinostomy under local anaesthesia - Limbu, Ben; Lyons, Hannah S; Shrestha, Mohan Krishna; Tabin, Geoffrey C; Saiju, Rohit (Nepalese Journal of Ophthalmology, 2019)
Introduction: The first line treatment for nasolacrimal duct obstruction (NLDO) is external dacrocystorhinostomy (DCR). Following DCR, patients are required to return to Tilganga Institute of Ophthalmology (TIO) six weeks postoperatively for the removal of a silicone stent. As the majority of patients travel large distances at significant cost to reach TIO, most often patients remain within Kathmandu during this six weeks interval. This places a large financial burden on patients.Methods: A randomized controlled trial was designed to compare patient outcomes after early (two weeks postoperatively) versus standard (six weeks postoperatively) removal of silicone stents. 50 selected patients were randomized into two equal groups.Results: At the time of publication, 31 patients (14 in group A and 17 in group B) had completed three months follow up. A success rate of 92.9% was noted in Group A and a success rate of 94.1% observed in group B. No significant difference was found between the two groups for success rate and rate of complications.Conclusion: Early tube removal post DCR appears to cause no significant difference in outcome or complication rates compared to standard tube removal.